Senkaku Islands Dispute Between China And Japan In East China Sea Review From International Law - Maulida Hadry Sa'adillah (Journal of Law Science, 2020)
Territorial disputes are problems that often become a problem for countries in the world. Later the world was presented with a territorial dispute between China and Japan. The dispute is over ownership of a group of islands in the East China Sea, the Senkaku Islands, which are thought to have the largest oil and gas reserves in Asia. International law for several centuries has continued to develop in regulating the issue of determining the sovereignty of a disputed territory. Regarding the archipelagic dispute, the question arises about how the state's sovereignty over the sea area according to international law is? How are territorial disputes resolved according to international law? And how about the settlement of the Senkaku Islands dispute between China and Japan according to international law?. The research method used is library research or normative research, namely by selecting and collecting data from various books, scholarly opinions, dictionaries, encyclopedias and international legal literature related to thesis writing. According to Article 38 of the UN Charter, the sources of international law consist of international treaties, international customs, principles common law recognized by civilized nations, court decisions and doctrines of scholars. An international territorial dispute is a dispute or dispute between two countries fighting over a certain area, for example, over an island. The Senkaku Islands dispute between China and Japan has actually been going on for a long time. However, the situation that has developed recently has worried the international community. This dispute caused relations between the two countries to worsen with the occurrence of a number of incidents related to the seizure of ownership of the islands. Settlement of territorial disputes is regulated in the United Nations Charter and the 1982 Law of the Sea Convention. Dispute settlement according to the United Nations Charter requires states to resolve their disputes peacefully based on the principles of international law. The UN Charter also prohibits states from using violence in resolving their disputes as stated in Article 2 Paragraph 4. While the 1982 Law of the Sea Convention provides several dispute resolution mechanisms to deal with problems that occur in the sea area.